Os saberes da formação de professores da educação de jovens e adultos do campo do Estado de Pernambuco - Melo, Ivanise Simplicio de (2019)
This thesis aims to recognize and analyze the knowledge learned by EJA CAMPO-PE teachers in the GEPEC-PE training process, which aims at an educational practice constituted by elements of teaching knowledge that promote the "awareness" of the subjects in the field of the need to fight for right to education, specifically the field education. We try to answer the following problem: What knowledge of EJA CAMPO / PE teachers learned in the field of GEPEC training? Its main objective is to recognize and analyze the knowledge about Field Education and Popular Education and its materialization in teaching practice. The specific objectives are: 1- To recognize the principles and political-philosophical foundations of Field Education and Popular Education present in the formation of GEPEC; 2 - Recognize the knowledge learned from the teachers of EJA CAMPO / PE from the formation of origin and continuing training of the GEPEC; 3- Analyze the relation of knowledge between the apprehended in the formation and its materialization in the teaching practice; 4- To contribute to the critical-social reflection of the practice of teacher training based on the knowledge required for the teaching performance in EJA (CAMPO). Its purpose is to analyze the process of Continuing Education of Teachers of the EJA CAMPO / PE seeking to apprehend the knowledge acquired in the training process. It assumes as a methodological reference the qualitative approach of the category of participatory action research analysis. In the theoretical framework we will take as reference the Paulo Freire thought - which is an epistemological anchor of our arguments in this study - and the studies on Field Education, enriched and increased by reflections generated from the interlocution, mainly, with; Caldart (2004, 2011), Streck (2003), Molina (2011, 2014, 2015, 2017), Souza (2009), Richardson (2003), Gauthier (1998) and Tardif (2002) popular education analysis; field education; knowledge of teaching practice, teacher training. Results: Recognize that the teachers of the EJA CAMPO appropriated in the process of formation of pedagogical knowledge that mobilized serve as support and basis for the materialization of the teaching practice in Field Education.